P0915PROTEIN ENERGY WASTING IS ASSOCIATED WITH A DECLINE IN MUSCLE PROTEIN SYNTHESIS IN CKD PATIENTS. (6th June 2020) - Saio, Michela; Sofia, Antonella; Russo, Rodolfo; Cipriani, Leda; Garibotto, Giacomo; Verzola, Daniela
Abstract: Background and Aims: Skeletal muscle is a highly adaptive tissue, however even small imbalances between protein synthesis and degradation can lead to substantial protein loss. Althought proteolysis plays a major role in the development of cachexia in CKD (chronic kidney disease), the responses of muscle protein metabolism to malnutrition had not been completely elucidated. We evaluated retrospectively the results of kinetic studies of protein turnover estimated by the forearm perfusion method associated with H2phenylalanine kinetic, obtained in CKD patients and controls in the last 25 years. Method: We analyzed 59 forearm H 2 phenylalanine kinetic studies obtained in 14 controls (C) (M 11, F 3) and 45 patients with CKD, of whom 15 (M 10, F 5) were on conservative treatment (CKD stage IV-V), 16 (M 14, F 2) under maintenance hemodialysis (HD), 14 (M 12, F 2) in peritoneal dialysis (DP); all subjects were on non-restricted protein/calorie (0.8-1.1 g/kg and 28-32 kcal/kg, respectively) diets. Ten (M 9, F 1) HD patients had Protein Energy Wasting. Acidosis was corrected in all patients (HCO3 24.2±1.9 mmol/L) and studies were performed in the post-absorptive overnight fasted state at rest. Results: Overall, Muscle protein synthesis and degradation were similar (p=NS) in patients and controls. Protein net balance was reduced in patients with PD and those with CKD Stage IV-V (p <0.003 - p <0.014) indicating a reduced catabolic state and nitrogen conservation. However PEW HD patients showed reduced rates of protein synthesis and degradation (p <0.048 and p <0.04 respectively). In addition the efficiency of muscle protein turnover, a parameter expressing muscle's ability to reuse amino acids derived from degradation into protein synthesis, was significantly reduced in HD PEW patients vs. controls (55.5 vs. 61.2 %, p <0.018, respectively) and vs. not malnourished patients in conservative treatment (70.1 % p <0.0025) or in PD (74.6 % p <0.005). Conclusion: In CKD patients, in absence of acidosis, muscle is able to increase the efficiency of protein metabolism for the maintenance of nitrogen balance. However, in PEW patients, combined alterations of protein synthesis and degradation proceed together to a reduced efficiency of amino acids recycled into protein synthesis and contribute to maintaining wasting. These data also suggest that calorie/protein requirements of CKD patients with PEW may be higher than currently theorized.